Pink lemonade cake murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery, 2023)
In this irresistible mystery from New York Times and USA Today bestselling author Joanne Fluke, Hannah Swensen is at the center of a lively summer fest with fun for everyone in Lake Eden, Minnesota—including a cold-blooded murderer ... The Tri-County Summer Solstice Celebration has come to town, and even among local artisans, athletes, and marching bands, Hannah attracts fans of her own while serving lip-smacking pink lemonade desserts. But the mood sours when a body turns up, leading revelers to wonder if the festivities mark both the longestday of the year and the deadliest ... A retired professional MLB player has met a terrifying end—and, considering the rumors swirling about his past, the list of suspects could fill a small stadium. Among them could soon be Delores, Hannah's mother, who publicly held a grudge against the victim after he infamously dunked her in the tank at a previous county fair ... Now, with her mother's innocence on the line, a life-changing announcement at The Cookie Jar, and a plethora of desserts to bake, Hannah can't afford to strike out as she begins a dangerous investigation into the ruthless killer who's truly in a league of their own ... Features Over a Dozen Cookie and Dessert Recipes from The Cookie Jar!